Characterization of the Volatile Profile of Bee Venom from Different Regions in Türkiye Using Gas Chromatography-Mass Spectrometry - Meral Kekeçoğlu; Onur Güneşer; Sevgi Kolaylı; Buket Aydeniz-güneşer (Journal of Agricultural Sciences)
The volatile organic compounds of bee venoms from four different populations of Apis mellifera anatoliaca, came from different regions in Türkiye, were analyzed using solid phase microextraction technique combined with gas chromatography-mass spectrometry. A total of 144 volatile compounds were identified in the bee venom samples. The identified volatile compounds included esters, terpenoids, alcohols, acid esters, aldehydes, ketones, and hydrocarbons. It was determined that ester-type volatile compounds characterized the bee venom obtained from the Central Anatolia Region, while bee venom from the Western Black Sea Region had a higher amount of volatile terpenes with spicy and woody aromas. Further studies are required to understand the volatile profile of bee venom, which consists of plant and animal secondary metabolites.